The role of crowdion mass transfer in relaxation processes near hard concentrators - Kononenko, V.G.; Bogdanov, V.V.; Turenko, A.N.; Volosyuk, М.А.; Volosyuk, А.V.; Karazin, V.N. (Вопросы атомной науки и техники, 2016)
Mechanisms of stress relaxation in KCl single crystals around hard corundum inclusions have been studied. The samples for the investigation were prepared by alloying the corundum balls into the single crystal. During the subsequent cooling of the system from the crystal melting point (1049 К) to room temperature (293 К), the ball indentation of the crystal was carried out. Dislocation structures around the balls of different sizes (from 2 to 20 m) were analyzed at various cooling temperatures (cooling times were from 2 to 708 min). It has been shown that the observed number of dislocation loops (taking into account their diffusion dissolving under cooling) has transferred not more than a half of the total dilatation volume. In this connection it is assumed that not less than a half of the mass transfer process is realized by a crowdion mechanism. Исследованы механизмы релаксации напряжений в монокристаллах KCl вокруг жестких сферических включений из корунда. Образцы для исследования получались методом вплавления шариков корунда в мо- нокристалл. В процессе последующего охлаждения системы от температуры плавления кристалла (1049 К) до комнатной (293 К) происходило индентирование кристалла шариком. Анализировались дислокационные структуры вокруг шариков разных размеров (от 2 до 20 мкм) при различных скоростях охлаждения (время охлаждения от 2 до 708 мин). Показано, что наблюдаемым количеством дислокационных петель (с учетом их диффузионного растворения в процессе охлаждения) перенесено не более половины всего объема дила- тации. В связи с этим предполагается, что не менее половины требуемого массопереноса осуществлено краудионным механизмом Досліджені механізми релаксації напружень у монокристалах KCl навколо жорстких сферичних вклю- чень з корунду. Зразки для дослідження отримувались методом вплавлення кульок корунду в монокристал. У процесі подальшого охолоджування системи від температури плавлення кристала (1049 К) до кімнатної (293 К) відбувалося індентування кристала кулькою. Аналізувалися дислокаційні структури навколо кульок різних розмірів (від 2 до 20 мкм) при різних швидкостях охолоджування (час охолоджування від 2 до 708 хв). Показано, що спостережуваною кількістю дислокаційних петель (з урахуванням їхнього дифузійно- го розчинення в процесі охолоджування) перенесено не більше половини всього об'єму дилатації. У зв'язку з цим припускається, що не менше половини необхідного масопереносу здійснено краудіонним механізмом.